Cloning and characterization of a multidomain PARP14 construct - Chatzicharalampous,Constantinos (2023)
PARP14, a member of the PARP family that can modify target proteins with ADP-ribose has stimulated the interest of researchers as it is involved in a variety of diseases including cancer. While some structural and activity characterization has been conducted, it has not been yet expressed and purified as a single molecule, instead it was examined in small constructs that include several of its domains separately. It contains multiple domains, the RNA recognition motif (RRM), three tandem macrodomains, a WWE and an ART catalytic domain (ADP-ribosylation). In this study a suspected region of the protein that could be responsible for aggregation and contamination generation, was substituted (using Gibson-assembly cloning), by a soluble SUMO-tag to express PARP14 as a single molecule, excluding the region starting from RRM until the N-terminal macrodomain. The SUMO-PARP14 was also studied from structure and activity perspective to approximate the characterization of the wild-type PARP14. The protein purification steps utilized were Immobilized Metal Affinity Chromatography, Anion exchange chromatography and Size Exclusion Chromatography. Negative staining was used to visually assess the protein structure in solution to confirm that it is suitable to be observed using cryo-EM in the future. Western blots and the MacroGreen plate assays were used to test whether SUMO-PARP14 preserves the ART activity, by monitoring the signal generated from ADP-ribosylated targets after treatment with an HRP-Streptavidin and an ADP-ribose binding macrodomain-GFP, respectively. SARS-CoV-2-NSP3-MAC1 inhibitory compounds were also tested against PARP14 macrodomain 1 due to structural homology, to determine if there is inhibition so that they could be used as ligands in the future for cryo-EM or crystallography. The methods used for the drug assessment were Western blot and Differential Scanning Fluorimetry. Ultimately, SUMO-PARP14 was successfully expressed with low signs of aggregation and contamination, and it was decided that it can be used after purification optimizations in cryo-EM. The protein retains the wild-type ART catalytic and macrodomain 1 (M1) glycohydrolytic activity (which was firstly experimentally confirmed in this study). As a confirmation that structural homologues of PARP14 M1 have glycohydrolytic capacity, PARP9 M1 which is its closest phylogenetic homologue, was assessed and determined that also has the same activity. Further, all compounds tested against PARP14 M1 were found to destabilize the protein structure observed through Tm shifts. Concluding, SUMO-PARP14 is a suitable construct to approximate the structure and activity of wild-type PARP14 as it can be highly pure with no significant aggregation present.
Keywords: ADP-ribosylation; Biochemistry; Glycohydrolase; Macrodomain; MacroGreen; PARP